Efflux Pump Inhibitors as a Broad-Spectrum Strategy to Combat Multidrug Resistance Acenitobacter Baumanii - Abdulazeez, Ayat Alaaeldin; Jaafar, Zainab Salim (Technium BioChemMed, 2024)
The World Health Organization (WHO) identifies A. baumannii as one of the most resistant pathogens. Over the past few years, there has been a significant rise in its resistance to a wide array of antibiotics. Multidrug resistance is attributed to several mechanisms, with efflux pumps being the most notable. Recently, the development of new treatment strategies to tackle A. baumannii infections has shown great promise. This review focuses on the various families of efflux pumps in A. baumannii and explores innovative therapeutic options that have emerged over the past four years. Specifically, we emphasize synthetic and natural efflux pump inhibitors (EPIs), nanoparticles, bacteriophage therapy, and antimicrobial peptides (AMPs) as part of these novel strategies.